Defining trends of migration policy of the European Union in the conditions of the newest inclusions in regional security: political and legal aspects - Hrubinko, Andrii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The article analyzes the main features and trends in development of the EU migration policy, challenges and threats to individual member states and the unification as a whole from the growth of the migration wave to Europe. Stretching XX and XXI migration processes have grown to unprecedented scale. The topic of migration and the problems of regulation became the reason for the political discussions within the framework of the European Union. During the last migratory crisis, which rocked around in 2015, the internal and external superinteractions between the countries of the European Union became even more promising. In the conclusion, it is argued that in modern conditions, when one of the most important tasks of the new millennium is the creation of a space of freedom, security and law and order in Europe, the strengthening of the criminogenic nature of illegal immigration necessitates the development of a common comprehensive migration strategy within the EU and the implementation of joint activities. The lack of protection from the viral problems of illegal migration has become especially evident in the course of terrorist acts, the victims of which in Europe are thousands of people. Illegal migration is more and more often seen as one of the youngsters of the expansion of international terrorism. It is important to note that everyday witness in the European regions has so deeply taken on the tradition of freedom and security, promoted by political witness, that security has become one of the most important cultural values of Europe. In the early 1990s vibrating fearful of freedom, now the Europeans are more and more likely to pass the test safely. In other words, illegal immigration is tightly intertwined in the sphere of national and special security.